Sprouty2/4 deficiency disrupts early signaling centers impacting chondrogenesis in the mouse forelimb - Dalecka, Linda; Hruba, Eva; Andrasova, Marketa; Steklikova, Klara; Pavlikova, Zuzana; Kucerova, Klara; Szotkowska, Tereza; Bartos, Martin; Buchtova, Marcela; Tucker, Abigail Saffron; Hovorakova, Maria (JBMR plus, 2025)
The FGF signaling pathway plays an important role in the regulation of limb development, controlling cell migration, proliferation, differentiation, and apoptosis. Sprouty proteins act as antagonists of the FGF pathway and control the extent of FGF signaling as part of a negative feedback loop. Sprouty2/4 deficient mice evince defects in endochondral bone formation and digit patterning in their forelimbs, with pathogenesis recently related to ciliopathies. To understand the mechanisms behind these pathologies, the limb defects in Sprouty2+/-;Sprouty4-/- male and female mice were characterized and correlated to the dynamic expression patterns of Sprouty2 and Sprouty4, and the impact on the main signaling centers of the limb bud was assessed. Sprouty2 and Sprouty4 exhibited dynamic expressions during limb development. Interestingly, despite similar expression patterns in all limbs, the hindlimbs did not evince any obvious alterations in development, while the forelimbs showed consistent phenotypes of variable severity. Prenatally as well as postnatally, the left forelimb was significantly more severely affected than the right one. A broad variety of pathologies was present in the autopodium of the forelimb, including changes in digit number, size, shape, and number of bones, hand clefts, and digit fusions. Ectopic ossification of bones and abnormal bone fusions detected in micro-CT scans were frequently observed in the digital as well as in the carpal and metacarpal areas. Sprouty2+/-;Sprouty4-/- limb buds showed patchy loss of Fgf8 expression in the apical ectodermal ridge, and a loss of tissue underlying these regions. The zone of polarizing activity was also impacted, with lineage analysis highlighting a change in the contribution of Sonic hedgehog expressing cells. These findings support the link between Sproutys and Hedgehog signaling during limb development and highlight the importance of Sprouty2 and Sprouty4 in controlling early signaling centers in the limb.
Keywords: micro-CT; ciliopathy; FGF signaling; RTKs; autopodium pathologies; zone of polarizing activity; limb patterning; genetic animal models; Shh; apical ectodermal ridge